Narrating African Futures : Prospective, Counter-Factual History and Speculative Fiction - (:unkn) unknown (My University, 2020)
The question of Africa’s future has, for a long time, been an essential geopolitical and economic issue, and treated as such in a wide variety of speeches and visual productions. Economists, historians, philosophers, authors and artists have thus developed innovative ways to depict and talk about the future of Africa, generating utopian and dystopian ideas, depending on the prevailing afro-optimism or, on the contrary, afro-pessimism. Thus, it appears that, in reality, discourses that are very different do share images, arguments, or similar narrative modalities that a literary and newsworthy analysis could reveal so as to highlight which common hypotheses shape the ways of thinking, imagining and describing the future of Africa. We shall be presenting some dominant portrayals and topics from the 19th century to the present day after recalling some of the essential information regarding the African continent, so as to help understand the central place that it occupies today in the imagination, as well as in economic and socio-political forward-thinking: for example, from the fear of Islam among European authors, to the hope of a reversal of world order in aid of Africa among African and Afro-American writers. We will then address the place that Africa holds in science-fiction and contemporary visual culture, from novels by the American Mike Resnick and his exponential development of original science-fiction, and in African literature and cinema, including the universe of comics, and notably the popular figure of the Black Panther. We will thus show how the universal success of this graphic and cinematographic series is precisely due to a certain number of key elements being condensed which can, in contrast, be dispersed differently according to cultural or national traditions that prevail on both sides of the Atlantic, or from one African country to another (for example, from Nigeria to South Africa).
Keywords: African Research